2015
DOI: 10.1111/1750-3841.12753
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Characteristics of French Fries Produced by Deep Fat Frying and Air Frying

Abstract: Air frying is being projected as an alternative to deep fat frying for producing snacks such as French fries. In air frying, the raw potato sections are essentially heated in hot air containing fine oil droplets, which dehydrates the potato and attempts to impart the characteristics of traditionally produced French fries, but with a substantially lower level of fat absorbed in the product. The aim of this research is to compare: (1) the process dynamics of air frying with conventional deep fat frying under oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 47 publications
6
61
1
4
Order By: Relevance
“…9 which will lower the breaking resistance. Other studies confirm this for the investigated time interval; for larger time intervals (N5 min) the breaking force will eventually increase again due to a significant crust being formed (Lima & Singh, 2001;Teruel et al, 2015). There are no differences in the maximum force at breakage for the frying temperatures of 150, 165 and 180°C, which indicates that the hardness of the fry is mostly determined by the overall moisture content in this temperature range.…”
Section: Maximum Forcesupporting
confidence: 61%
“…9 which will lower the breaking resistance. Other studies confirm this for the investigated time interval; for larger time intervals (N5 min) the breaking force will eventually increase again due to a significant crust being formed (Lima & Singh, 2001;Teruel et al, 2015). There are no differences in the maximum force at breakage for the frying temperatures of 150, 165 and 180°C, which indicates that the hardness of the fry is mostly determined by the overall moisture content in this temperature range.…”
Section: Maximum Forcesupporting
confidence: 61%
“…In a study by Teruel et al (2015), the deep-fried fries were found to be less/moderately hard. This is difficult to get as it may vary with regard to the region, country, town, and even type of consumers.…”
Section: Texture Score Of Sweetpotato Friesmentioning
confidence: 96%
“…According to Teruel, Gordon, Linares, Ahromrit, and Niranjan (2015), some level of browning occurs during deep frying in oil. Again, this indicates that the frying conditions used did not cause a lot of browning but were just enough to cook all starches in the sweetpotato.…”
Section: Appearance Score Of Sweetpotato Friesmentioning
confidence: 99%
“…Due to its operational simplicity, economic viability, high versatility and its ability to create distinctive sensory characteristics in foods that are highly appreciated by consumers, frying is extensively employed in both domestic and industrial sectors (Teruel et al, 2015). Continuous and repeated use of frying oil is a common practice to cut expenses (Aladedunye & Przybylski, 2013).…”
Section: Introductionmentioning
confidence: 99%